Perspective on Metamaterial of Energy Device Application - Habibi, Fathan Akbar Nur; Putra, Septia Eka Marsha (Journal of Batteries for Renewable Energy and Electric Vehicles, 2024)
Metamaterials have shown great potential for energy device applications, including energy harvesting, storage, and transmission. However, implementing metamaterials in energy devices presents several challenges, such as complex design and fabrication, narrowband limitation, and integration with existing technologies. Despite these challenges, ongoing research and development in the field of metamaterials is focused on exploring new materials, designs, and applications for metamaterials in energy devices. Specific examples of energy devices that use metamaterials include solar cells, wind turbines, thermal management systems, energy storage systems, wireless power transfer systems, and 3D metamaterials for energy harvesting. The use of metamaterials in energy devices has the potential to revolutionize the energy sector by enabling more efficient and sustainable energy generation, storage, and transmission systems.